Lophopidae of the amazon basin with keys to new world genera and species (HOMOPTERA: FULGOROIDEA). - O'brien, Lois; Penny, Norman D.; Arias, Jorge Ramon (Acta Amazonica, 1986)
The two especies of Lophopidae found in the lowland Amazon Basin, Hesticus rufimanus, (walker) and H. sanguinifrons Muir, are redescribed and their geographical distributions given. Keys are provided to genera of New World lophopidae, and to species of Hesticus .